(untitled) (Journal of the College of Basic Education, 2024)
This paper presents a psychoanalytic exploration of woman’s madness in selected short stories of Shirley Jackson. Through the analytical lens of Elaine Showalter’s concept of the "female malady," this study delves into the intricate layers of psychological complexity experienced by the female protagonists in two selected short stories "The Daemon Lover," which reveals the protagonist’s obsession with her lover, and "The Tooth," which explores the interplay of anxiety, feminine identity, and societal pressure. The study is qualitative one, it is going to answer whether female’s madness is an inherited treat in women’s mentality or it is acquired due to the social pressures imposed upon women. A psychological theory is applied to demonstrate how seemingly mundane events can evoke profound psychological turmoil. This analysis uncovers the ways in which patriarchal system, individual psychology, and societal norms. The characters’ experiences are dissected through the lens of suppressed desires, societal expectations, and the negotiation of identity within restrictive contexts.